Three-dimensional network-like amorphous NiCo-LDH nanofilms coupled with Co3O4 nanowires for high-performance supercapacitor. Issue 17 (1st December 2019) - Zhu, Yuanyi; An, Shengli; Cui, Jinlong; Qiu, Hengrui; Sun, Xuejiao; Zhang, Yongqiang; He, Wenxiu
Abstract: A network-like structure consisting of an amorphous nickel–cobalt layered double hydroxide nanofilm anchored to Co3 O4 nanowires (Co3 O4 /NiCo-LDH) is grown on nickel foam via hydrothermal reaction and electrochemical deposition. The complex interlocking network-like structure provides three-dimensional interconnected porous channels for electron transport and ion diffusion, and provides optimal access to active sites; this results in rapid Faradaic redox reactions. This intriguing advantage gives the optimal Co3 O4 /NiCo-LDH electrode outstanding electrochemical performance, with an ultrahigh specific capacity of 1067 C g -1, and high rate performance, with 73.28% capacity retention at 20 A g -1 . When it is combined with an activated carbon (AC) electrode, the Co3 O4 /NiCo-LDH//AC device exhibits a maximum energy density of 74.4 Wh kg -1 at a power density of 989 W kg -1 and excellent cycling stability, with 91.57% retention after 7000 cycles. This study provides new options and an important foundation for rational design of network-like structures for application in hybrid supercapacitors.